Program Pengembangan dan Pemenuhan Hak Anak di Lembaga Pemasyarakatan Tanjung Raja Golongan II A Yang Bertentangan Dengan Hukum - Taufiq Idris, Muhammad; Saputra, Muhammad Adi; Rahmatullah Ayu Hasmiati; Pettanase, Ismail (CV. Doki Course and Training, 2023)
The program for developing and upholding the rights of children associated with the law in class II A Tanjung Raja prison was a topic of concern, and study was conducted as a result for the purpose of addressing it. How tutoring for youth who break the law is implemented in Class II A Tanjung Raja Prison. and How to Comply with Children's Legal Rights in Class II A Children's Correctional Institution Tanjung Raja. The form of sociological legal research, the nature of the descriptive analytical research, and the data used in the study were chosen to explore the aforementioned issues. Primary data was gathered by conducting interviews with relevant individuals, especially prison officers. Explanations and main and secondary legal resources like dictionaries, encyclopedias, and others are the ones with the most precise legal information. Based on the research's findings, specifically: According to Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, coaching of children who are prisoners is oriented to social values, and in the Class IIA Tanjung Raja prison, intramural treatment is carried out, guidance is provided to children who are in conflict with the law. Observation of children's legal rights in Tanjung Raja Class II The construction of a children's prison takes into account the existing infrastructure and amenities, and one of those fulfillments is the ability to allow children to have family visits. Because of worries that it may hinder the spread of Covid 19, the execution of children's rights in Tanjung Raja Prison continues to go well and is approved selectively throughout this epidemic, especially for temporary inmates.